Peningkatan Proses Pembelajaran Tematik Terpadu Dengan Strategi Card Sort di Sekolah Dasar - Akmal, Hanifah Husna; Harni, Harni (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study is to describe the improvement of the integrated thematic learning process by using a card sort strategy in Class IV SD. The type of research is a classroom action research that use qualitative and quantitative approache.The subjects of this researchare teachers and fourth grade elementary school students consist 26 people. The result showed an increase in: a) The average implementation aspects of the teachers 83% (good) and the second cycle 92% (very good), b) The average implementation aspect of the first cycle students 81% (good), and the second cycle 92% (very good), c) attitude assessment in cycle I obtained a good attitude and cycle II gained a very good attitude d) Assessment of aspects of knowledge in cycle I obtained 75 (enough) and cycle II 85 (Good). e) assessment of the aspects of skills in cycle I obtained 80 (enough) and this cycle II was 87 (good). Keywords: Integrated Thematic: Card Sort Strategy